Vasospastic Angina and its Contemporary Review of Pathophysiology, Diagnosis and Management - Laksono, Sidhi; Suhandoko, Lidya Pertiwi (UNUSA Press, 2024)
Introduction: Nearly half of patients who present with angina have non-obstructed coronary arteries. Patients with chest pain in the absence of obstructive coronary artery disease (CAD) remain a challenge. These patients undergoing invasive coronary angiography do not have epicardial coronary disease obstructive enough to explain these symptoms. This condition is potentially serious and can sometimes trigger severe arrhythmia resulting in ventricular fibrillation and sudden death. However, the pathophysiological mechanisms underlying this phenomenon are incompletely understood, which has resulted in limited therapeutic options for patients afflicted with this condition. This review article provides a comprehensive summary of the underlying pathophysiological mechanisms of VSA and the current therapeutic options. We also appraise the current diagnostic approach in patients with suspected VSA. Result: Coronary microvascular tone and subsequently, its blood flow is regulated through various vasodilating and vasoconstricting mechanisms. Coronary endothelial dysfunction and vascular smooth muscle hyperreactivity are proposed mechanism causing coronary artery spams. This may cause transient ST-Elevations, malignant arrhythmias and significant heart blocks. Various non-invasive and invasive exams may identify and differentiate these variant anginas. Conclusions: VSA can be diagnosed accurately and safely in the catheter laboratory. The mainstay of management is pharmacological treatment.